Evaluation of various types of imported emitters used in drip irrigation systems in Libya - علي عثمان الغصني (Journal of Pure & Applied Sciences, 2017)
This study was carried out to evaluate various types of imported emitters used in drip irrigation systems in Libya. Two types of point source emitters were evaluated; namely on-line emitters and in-line emitters. One model of the in-line emitters were evaluated. The evaluated model of the in-line emitters were manufactured in Egypt. In this model, the emitters were designed to be attached to the lateral tube line from two sides. Three models of on-line emitters were tested in this study. The evaluated models of on-line emitters were manufactured in Egypt, Greece, and Italy. A sample of fifty new emitters from each model were tested in laboratory. Each emitter was operated alone for twenty minutes at a reference pressure head of 10.7 meters. The discharged water from each emitter was collected and measured. The coefficient of manufacturing variation for each sample was calculated from the discharge data (converted to liter per hour) of the samples. To determine emitter discharge exponent for each sample, two emitters of each type were operated (alone) at two different pressure heads; namely 2 and 5 meters. The results showed that the coefficient of manufacturing variation was 0.32 for the in-line Egyptian emitters and 0.23, 0.15 and 0.11 for the Greek, Egyptian and Italian on-line emitters, respectively. According to the American Society of Agricultural Engineers, the in-line Egyptian emitters and the Greek on-line emitters can be classified as unacceptable whereas the on-line emitters were classified as marginal and poor quality for Italian and Egyptian on-line emitters, respectively. This classification rely on emitter coefficient of manufacturing variation which was determined in this study. The emitter discharge exponents were 0.63 for the Egyptian in-line emitters and 0.43, 0.40 and 0.31 for the on-line emitters imported from Egypt, Greece and Italy, respectively. Therefore, it can be concluded that the discharges of the on-line tested emitters are less sensitive to variation in operating pressure than the in-line Egyptian emitters. This is due to low emitter discharge exponents of the on-line emitters.